Evolving Dynamics of Societal Security and the Potential for Conflict in Eastern Ukraine - Маляренко, Тетяна Анатоліївна; Маляренко, Т. А.; Маляренко, Татьяна Анатольевна; Maliarenko, Tetiana A.; Malyarenko, Tetyana; Гелбрейт, Девід; Гэлбрейт, Дэвид; Galbreath, David J.; Galbreath, David (Informa UK Limited, 2020)
In this essay we argue that changes in political structures in post-Soviet Ukraine have affected the potential for conflict during transition. Relying on organisational theory to determine the potential for conflict in Ukraine, we argue that this potential is structurally determined by the changing character of societal relations within and beyond Ukraine. The potential for conflict was always present in post-Soviet Ukraine, but this essay examines the facts of when, how and why conflict happened, and how it was related to weak state institutions, "centre–periphery" relations and an unsettled relationship with Russia. Relying on our analytical framework, we conclude that the conditions for further conflict greatly outweigh the conditions for peace.

У цьому нарисі ми стверджуємо, що зміни в політичних структурах пострадянської України вплинули на потенціал конфлікту під час перехідного періоду. Спираючись на організаційну теорію для визначення потенціалу конфліктів в Україні, ми стверджуємо, що цей потенціал структурно відзначається мінливим характером суспільних відносин в Україні та за її межами. Потенційний конфлікт завжди був присутній у пострадянській Україні, але в цьому нарисі розглядаються факти, коли, як і чому стався конфлікт, і як він був пов'язаний із слабкими державними інституціями, відносинами "центр-периферія" та неврегульованими відносинами з Росією . Спираючись на нашу аналітичну базу, ми дійшли висновку, що умови для подальшого конфлікту значно переважають умови для миру.

В этом эссе мы утверждаем, что изменения в политических структурах в постсоветской Украине повлияли на конфликтный потенциал в переходный период. Опираясь на организационную теорию для определения потенциала конфликта в Украине, мы утверждаем, что этот потенциал структурно определяется изменяющимся характером общественных отношений внутри и за пределами Украины. Потенциал конфликта всегда присутствовал в постсоветской Украине, но в этом эссе исследуются факты о том, когда, как и почему произошел конфликт, и как он был связан со слабыми государственными институтами, отношениями «центр-периферия» и неурегулированными отношениями с Россией. Опираясь на нашу аналитическую структуру, мы делаем вывод, что условия для дальнейшего конфликта значительно перевешивают условия для мира.
Galbreath D. Evolving Dynamics of Societal Security and the Potential for Conflict in Eastern Ukraine / D. Galbreath, T. Malyarenko // Europe-Asia Studies. – V. 72 (2). - Informa UK Limited, 2020. – P. 209-237.